Kesadaran masyarakat melakukan Jalan Kaki untuk kebugaran - Veni, Maria Okta; SUpriatna, Eka Eka (Universitas Tanjungpura, 2023)
Walking exercises can improve cardiovascular and lung fitness and reduce the risk of heart disease and stroke. Lack of exercise can cause health problems that cause bone density to decrease drastically, resulting in the loss of muscle mass. People want to exercise their encouragement and awareness of the importance of health in the body. Each individual has a different response to the importance of health, so it is not surprising that some people think that exercise is not important. This research aims to determine the level of awareness of people who regularly walk. The research method used is to fill out a questionnaire. The sample in this study used 35 respondents. The instrument used was a questionnaire distributed and filled in directly by respondents. The collected data was analyzed using descriptive statistics. Data analysis found that the level of health for those who exercise regularly is sufficient and is dominated by everyone's awarenes